2022
DOI: 10.7554/elife.63776
|View full text |Cite
|
Sign up to set email alerts
|

Intravital deep-tumor single-beam 3-photon, 4-photon, and harmonic microscopy

Abstract: Three-photon excitation has recently been demonstrated as an effective method to perform intravital microscopy in deep, previously inaccessible regions of the mouse brain. The applicability of 3-photon excitation for deep imaging of other, more heterogeneous tissue types has been much less explored. In this work, we analyze the benefit of high-pulse-energy 1 MHz pulse-repetition-rate infrared excitation near 1300 and 1700 nm for in-depth imaging of tumorous and bone tissue. We show that this excitation regime … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Due to its deeper anatomical location, RGC axons in the optic nerve head are inaccessible using two-photon live imaging. Given that the optic nerve head undergoes early pathological changes in glaucoma, future efforts are warranted to monitor mitochondrial movement by in vivo optical microendoscopy (Barretto and Schnitzer, 2012) or three-photon excitation intravital microscopy (Bakker et al, 2022). Mitochondrial volume assessment in single axons was performed in double transgenic mice (Thy1-CFP.MitoS::Thy1-YFP), and although we did not detect noticeable differences between single and double transgenic mice, we cannot rule out potential limitations inherent to the use of the same promoter.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Due to its deeper anatomical location, RGC axons in the optic nerve head are inaccessible using two-photon live imaging. Given that the optic nerve head undergoes early pathological changes in glaucoma, future efforts are warranted to monitor mitochondrial movement by in vivo optical microendoscopy (Barretto and Schnitzer, 2012) or three-photon excitation intravital microscopy (Bakker et al, 2022). Mitochondrial volume assessment in single axons was performed in double transgenic mice (Thy1-CFP.MitoS::Thy1-YFP), and although we did not detect noticeable differences between single and double transgenic mice, we cannot rule out potential limitations inherent to the use of the same promoter.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…[ 56 ] Past research demonstrated the feasibility of four‐photon fluorescence microscopy (4PM) in biological tissues based on quantum perturbation theory and measurements. [ 53,57 ] Meanwhile, the longer excitation wavelength in 4PM may cause deeper penetration and better resolution in brain tissue. However, the advantage of 4PM with excitation of NIR‐II light in terms of deep brain imaging is needed further investigation, due to the exist fluorophores with small four‐photon adsorption cross‐section.…”
Section: Nir‐ii Bioimaging Systemsmentioning
confidence: 99%
“…The pump and OPA wavelengths were centered at 1030 and 1320 nm respectively, resulting in TSFG and THG wavelengths at λ TSFG 1 ¼ 370 nm, λ TSFG 2 ¼ 402 nm and λ THG 2 ¼ 440 nm. We remind that OPA-based excitation at 1 MHz is expected to provide an 80 2 increase in THG efficiency compared to 80 MHz OPO excitation with similar pulse durations and average power, enabling to work at larger depths by progressively increasing the power delivered to the tissue surface 59 . One difference with the transmission geometry used in the previous section is that the epidetected signals correspond to THG and TSFG light that is mostly forward-generated and then scattered back towards the objective by tissue structures underneath the imaging plane.…”
Section: Deep-tissue Blood Imaging In Adult Zebrafish Brainmentioning
confidence: 99%